2013
DOI: 10.1530/eje-12-0753
|View full text |Cite
|
Sign up to set email alerts
|

Active acromegaly is associated with decreased hs-CRP and NT-proBNP serum levels: insights from the Belgian registry of acromegaly

Abstract: Objective: Patients with active acromegaly have an increased prevalence of cardiomyopathy and heart failure but a less than expected risk of coronary artery disease, considering the frequent association of diabetes mellitus and hypertension. We examined whether changes in high-sensitive C-reactive protein (hs-CRP) and N-terminal pro-brain natriuretic peptide (NT-proBNP) might contribute to this phenomenon. Design and methods: Two hundred patients of the Belgian acromegaly registry (AcroBel) were divided in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…Considering CV risk in acromegaly, Verhelst et al analyzed two specific markers of CV risk among acromegalic patients, subdivided into a controlled disease group (−2 < IGF-1 Z-score < +2) and an active disease one (IGF-1 Z-score > +2) [ 97 ]. They took into account highly sensitive CRP (hs-CRP), related to CVD and the N -terminal pro-BNP (NT-proBNP), diagnostic for congestive heart failure [ 97 ].…”
Section: Igf-1 and Adiponectin In Relation To Cardiovascular Diseamentioning
confidence: 99%
See 2 more Smart Citations
“…Considering CV risk in acromegaly, Verhelst et al analyzed two specific markers of CV risk among acromegalic patients, subdivided into a controlled disease group (−2 < IGF-1 Z-score < +2) and an active disease one (IGF-1 Z-score > +2) [ 97 ]. They took into account highly sensitive CRP (hs-CRP), related to CVD and the N -terminal pro-BNP (NT-proBNP), diagnostic for congestive heart failure [ 97 ].…”
Section: Igf-1 and Adiponectin In Relation To Cardiovascular Diseamentioning
confidence: 99%
“…Considering CV risk in acromegaly, Verhelst et al analyzed two specific markers of CV risk among acromegalic patients, subdivided into a controlled disease group (−2 < IGF-1 Z-score < +2) and an active disease one (IGF-1 Z-score > +2) [ 97 ]. They took into account highly sensitive CRP (hs-CRP), related to CVD and the N -terminal pro-BNP (NT-proBNP), diagnostic for congestive heart failure [ 97 ]. The authors found low levels of hs-CRP in active acromegalic patients compared to control subjects, indicating a lower CV risk in active disease, whereas high NT-proBNP values were reported in controlled patients compared to healthy subjects, suggesting a controversial role for such a marker.…”
Section: Igf-1 and Adiponectin In Relation To Cardiovascular Diseamentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies suggest that acromegalic patients do not have increased prevalence of coronary artery disease [ 49 , 50 ], carotid atherosclerosis, or carotid internal media thickness compared to normal subjects [ 49 , 51 ]. In a recent European study on 200 acromegalic patients matched with a control group, it was reported that patients with active acromegaly had significantly lower levels of high-sensitive C-reactive protein (hs-CRP) both compared with patients with controlled acromegaly and with a matched reference population [ 52 ]. Possibly, a lower hs-CRP may be linked to lower than expected prevalence of atherosclerosis in patients with active acromegaly, despite the presence of other risk factors such as insulin resistance and hypertension.…”
Section: Vascular Effects Of Gh and Igf-imentioning
confidence: 99%
“…In the literature, a few studies have shown increased oxidative stress and reduced antioxidant status in acromegaly [16]. In contrast, the role of subclinical inflammation on atherosclerosis in acromegaly is still contradictory because previous studies have shown that patients with acromegaly primarily have decreased [17] as well as unchanged [18] high sensitive C-reactive protein (hs CRP) levels.…”
Section: Introductionmentioning
confidence: 99%